Tumor Deposits as an Adverse Prognostic Indicator in Stage III Colon Cancer: A Multicenter Database Study - Jeeyou Kim, MD; Dong Woon Lee, MD; Ji Won Park, MD, PhD; Seung-Bum Ryoo, MD, PhD; Heung-Kwon Oh, MD, PhD; Rumi Shin, MD, PhD; Jin Sun Choi, MD; Min Jung Kim, MD; Sung-Chan Park, MD; Duck-Woo Kim, MD, PhD; Seung Chul Heo, MD, PhD; Sung-Bum Kang, MD, PhD; et al. (Annals of Surgery Open)
Objective:. We explored the oncological impact of tumor deposits (TDs) on colon cancer and proposed optimal modifications to the current staging system. Background:. In the existing American Joint Committee on Cancer colon cancer staging system, TDs are incorporated into the N category as N1c. When lymph node metastases (LNMs) are present, their number is considered to determine nodal stages, such as N1a/b or N2a/b, regardless of TDs. Methods:. 4212 patients with primary colon cancer who underwent surgical resection in the Seoul Colorectal Group (2010–2020) and 93,057 patients from the Surveillance, Epidemiology, and End Results*Stat database (2000–2017) were included in this study. Patients were classified according to the number of metastatic lymph nodes (LNs) (0/1–3/≥4) and the presence of TDs. Results:. TDs were significantly associated with left colon cancer, a higher T category, and vascular/perineural invasion. Patients with TDs had higher recurrence rates (23.1 vs 7.5%, P < 0.001). The TD-positive patients had notably worse overall survival (OS) and recurrence-free survival rates. The survival outcomes of TD-positive patients without LNM were inferior to those of TD-negative patients with LN1–3 (5-year OS: 78.9 vs 87.8%, P = 0.04). The survival outcomes of TD-positive patients with LN1–3 were similar to those of TD-negative patients with LN ≥4 (5-year OS: 87.0 vs 77.1%, P = 0.11). Survival outcomes obtained using the Surveillance, Epidemiology, and End Results *Stat database yielded consistent results. Conclusions:. TDs were associated with poor prognostic factors and had a significant impact on survival outcomes. The incorporation of tumor deposits into nodal classifications beyond the current N1c criteria may improve the staging system and more accurately reflect the recurrence and survival rates among patients with colon cancer. TD-positive in N1a or N1b could be categorized as N2.